2017
DOI: 10.1515/afepuc-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plyometrics on Jump Capabilities in Technical and Aesthetical Sports

Abstract: Summary:The aim of the study was to examine the effect of plyometric exercises on explosive strength of lower extremities in girls performing of technical and aesthetical sports. Experiment was carried out on three groups; artistic gymnasts (V G , n = 15; age = 12.4 ± 0.7 years), fitness girls (V F , n = 15; age = 13.8 ± 1.9 years) and dancers (V D , n = 15; age = 13.8 ± 2 years). To check, the control group of general population was involved in the study (V K , n = 15; age = 13.9 ± 1.5 years). Following tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Previous studies that observed the effect of training programs in the jump height of dancers have also obtained improvements in this variable with values pre-post diverging between 16.9 (2.9) cm and 18.9 (2.7) cm ( p < 0.001, d = 0.36: small ES) pre-post 30 weeks of a plyometric training program and in CMJ with arm swing dancers jumped 21.5 (3) cm vs. 25 (2.8) cm ( p < 0.001, d = 1.21: large), an ES equal to our findings in CMJ ( Mlsnová and Luptáková, 2017 ); 22.50 (4.21) cm and 25.47 (4.95) cm pre-post a 10-week modern and recreational dance exercise program and trunk and leg muscle strengthening exercises ( Stošić et al, 2020 ); 26.93 (2.78) cm and 27.35 (3.06) cm pre-post an 8-week protocol ( Tsanaka et al, 2017 ); and 29.3 (3.2) cm and 33.5 (3.7) cm with a significant improvement ( Escobar-Alvarez et al, 2019 ) aligned with our findings. Still, in studies without interventions, CMJ height values ranged between 23.34 (1.72) cm in dancers aged 15 (1.07) years ( Rojano-Ortega, 2020 ) and 28.29 (3.42) cm in dancers aged 18.94 (1.32) years ( Alvarez et al, 2020 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Previous studies that observed the effect of training programs in the jump height of dancers have also obtained improvements in this variable with values pre-post diverging between 16.9 (2.9) cm and 18.9 (2.7) cm ( p < 0.001, d = 0.36: small ES) pre-post 30 weeks of a plyometric training program and in CMJ with arm swing dancers jumped 21.5 (3) cm vs. 25 (2.8) cm ( p < 0.001, d = 1.21: large), an ES equal to our findings in CMJ ( Mlsnová and Luptáková, 2017 ); 22.50 (4.21) cm and 25.47 (4.95) cm pre-post a 10-week modern and recreational dance exercise program and trunk and leg muscle strengthening exercises ( Stošić et al, 2020 ); 26.93 (2.78) cm and 27.35 (3.06) cm pre-post an 8-week protocol ( Tsanaka et al, 2017 ); and 29.3 (3.2) cm and 33.5 (3.7) cm with a significant improvement ( Escobar-Alvarez et al, 2019 ) aligned with our findings. Still, in studies without interventions, CMJ height values ranged between 23.34 (1.72) cm in dancers aged 15 (1.07) years ( Rojano-Ortega, 2020 ) and 28.29 (3.42) cm in dancers aged 18.94 (1.32) years ( Alvarez et al, 2020 ).…”
Section: Discussionsupporting
confidence: 71%
“…Some studies observed the effect of training programs to improve jumping performance, either in dancers or in rhythmic gymnastics, which is the gymnastics discipline more equivalent to dance ( Wang et al, 2010 ; Piazza et al, 2014 ; Komeroski et al, 2016 ; Mlsnová and Luptáková, 2017 ; Tsanaka et al, 2017 ; Dobrijević et al, 2018 ; Skopal et al, 2020 ; Stošić et al, 2020 ). Focusing on dance, previous studies have applied for a specific strength training program, for 9 weeks, based on and adjusted according to the force-velocity profile of each dancer ( Escobar-Alvarez et al, 2019 ); evaluated whether a 9-week resistance training program could have a significant effect on the strength and power of the lower limbs in adolescent dancers ( Dowse et al, 2020 ); applied, for 10 weeks, a modern and recreational dance exercise program and trunk and leg muscle strengthening exercises in university dance students ( Stošić et al, 2020 ) and used their ballet classes, modified with a focus on lower-limb strength (reduction in bar duration (from 45′ to 20′) and the petit and grand allegro exercises at the beginning of center work, for 8 weeks, as an intervention to analyze jumping ability ( Tsanaka et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…12 6,7,10 , three studies included Artistic gymnasts 2, 12, 13 while 2 studies have not mentioned the type of gymnasts. 3,11 INTERVENTIONAL CHARACTERISTICS In total about 7 different interventional programs were studied in the included studies (Table 3) among which were Plyometric training, 6,3,11,13 core and plyometric training together 10 , Core training alone 7 and Neuromuscular training. 2 The duration of studies included range from 4 weeks to 12 months period with only one study of one-time intervention.…”
Section: Population Characteristicsmentioning
confidence: 99%
“…Among these studies one study has used force plates to measure the drop jumps (DJ) and CMJ 10 which has provided the most accurate results. Plyometric led to repeated stimuli of explosive training which in turn led to improvement of jumping abilities like Vertical jump 6 , Drop jump 2,11 , Countermovement jumps 3,13,11 and Squat jump 11 .…”
Section: Effect Of Exercise Training On Jumpsmentioning
confidence: 99%
See 1 more Smart Citation